2003
DOI: 10.1088/0953-8984/15/24/106
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization corrections to the coercive field in thin-film ferroelectrics

Abstract: Empirically the coercive field needed to reverse the polarization in a ferroelectric increases with decreasing film thickness. For ferroelectric films of 100 microns to 100 nanometers in thickness the coercive field has been successfully described by a semi-empirical scaling law. Accounting for depolarization corrections, we show that this scaling behavior is consistent with field measurements of ultrathin ferroelectric capacitors down to one nanometer in film thickness. Our results also indicate that the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
169
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(181 citation statements)
references
References 18 publications
(38 reference statements)
12
169
0
Order By: Relevance
“…Nevertheless, the stronger field compared to that in the Pt/PbTiO 3 /Pt structures also confirms the weaker screening effect of SrRuO 3 compared to Pt and other transition metals. 14 We note further that allowing the internal coordinates of the SrRuO 3 electrodes, especially those in the boundary layers, to relax together with the PbTiO 3 ions is crucial. When the SrRuO 3 ions are fixed in their ideal positions, we find only paraelectric structures for either of the PbTiO 3 terminations.…”
Section: Figmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the stronger field compared to that in the Pt/PbTiO 3 /Pt structures also confirms the weaker screening effect of SrRuO 3 compared to Pt and other transition metals. 14 We note further that allowing the internal coordinates of the SrRuO 3 electrodes, especially those in the boundary layers, to relax together with the PbTiO 3 ions is crucial. When the SrRuO 3 ions are fixed in their ideal positions, we find only paraelectric structures for either of the PbTiO 3 terminations.…”
Section: Figmentioning
confidence: 93%
“…To address this question, we turn now to look at the depolarizing field and screening effects in these systems. The depolarizing field was previously addressed in phenomenological studies, 5,14,23 and is shown to scale with the spontaneous polarization of the ferroelectrics, the screening length of the electrodes and the inverse ferroelectric film thickness. Hence the depolarizing field would be expected to be negligible only in very thick films.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12] As the dimensions (both lateral and vertical direction) of the perovskite layer decreases, the fundamental question of size dependence becomes crucial. From a theoretical point of view, two models have been traditionally used to describe size effects, namely an "intrinsic" effect 9,10,13 and a "depoling field" effect.…”
mentioning
confidence: 99%
“…10,17,18 Additionally a systematic increase in the coercive field is observed as the thickness is scaled down to 15 nm, in agreement with previous reports. 1,2,19 However for sub-10-nm-thick films the hysteresis loops were leaky, and not credible. Therefore we measured the polarization under pulsed probing conditions using an AFM based test setup.…”
mentioning
confidence: 99%